Ocular Straylight in Albinism - Kruijt, Bastiaan; Franssen, Luuk; Prick, Liesbeth J. J. M.; van Vliet, Johannes M. J.; van den Berg, Thomas J. T. P. (Optometry and vision science, 2011)
Albinism is an inherited disorder that affects the melanin biosynthesis pathway, which results in reduced or absent pigment formation. This may lead to increased light transmission through the iris and more reflected light from the fundus. Both these effects contribute to the occurrence of ocular straylight. One aim of this study is to determine whether and how increased iris transmission and fundus reflection in subjects with albinism contributes to the occurrence of ocular straylight. The other aim is to determine the effect that an iris print-contact lens (CL) could have in terms of reducing the occurrence of ocular straylight. Ocular straylight was quantified by means of the straylight parameter s and measured as a function of angle and wavelength in 17 subjects with different types of albinism, none of whom wore an iris print-CL. The measurements were then repeated with the subjects wearing an iris print-CL to reduce the iris transmission component and thus the occurrence of ocular straylight. The contributions of transmission and reflectance components were estimated for each individual. Straylight level increase varied from normal (s ≈9) to severe (8x). In 15 cases, the reflectance component contributed s >3 to up to s = 17. In eight cases, the transmission component contributed s >3 to up to s = 101. A significant reduction in straylight was observed using an iris print-CL in six subjects with elevated straylight values. In the other 11 subjects with albinism, the iris print-CL had no significant effect on straylight because of the low values of the transmission component. This study gives insight into the effects of transmission and reflectance on the total measured straylight occurrence in subjects with albinism. Subjects experiencing increased ocular straylight values may benefit significantly from wearing iris print-CLs because transmission of light through the natural iris may cause a significant increase in straylight.